Relationship between Classroom Environment and Moral Values of Secondary School Students (Journal of Social Sciences Review, 2023)
The present study aimed to investigate the relationship between the classroom environment of schools and the moral values of secondary school students. Specifically, the study focused on exploring the perceptions of secondary school teachers regarding the classroom environment and the levels of moral values exhibited by students. A sample of 1288 secondary school teachers was selected for the study, representing ten districts within the Khyber Pakhtunkhwa province. To ensure comprehensive representation, the sample included 200 secondary school teachers from each district. The selection of teachers was carried out using a non-random approach, with 100 teachers chosen from rural areas and 100 teachers from urban areas within each district. This sampling strategy aimed to capture a diverse range of perspectives on the classroom environment and its impact on students' moral values. In order to examine the relationship between the classroom environment and students' moral values, a correlation analysis was conducted. The results of the analysis revealed a significant positive relationship between the classroom environment and the moral values of students. This finding suggests that the classroom environment plays a significant role in shaping and influencing the development of students' moral values. The recommendations derived from the study offer practical implications for educators and policymakers to enhance the classroom environment and facilitate the cultivation of positive moral values among students.
Keywords: Classroom Environment; Moral Values; Secondary School Students; Secondary School Teachers